Effect of Cu(ATSM) on the expression and activity of ABC export proteins in killifish (Fundulus heteroclitus) kidney tubules - Kraus, Lisa; Fricker, Gert (Environmental toxicology and pharmacology, 2025)
ABC transporters are important for excretion of xenobiotics and metabolites into urine. They are sensitive to metallic pollutants like cadmium, mercury, zinc, or arsenic. Here, we show that copper (Cu(ATSM)) stimulates ABC transporter-mediated export in isolated renal proximal tubules from Atlantic killifish (Fundulus heteroclitus) with main focus on Mrp2. Transporter stimulation was reduced by cycloheximide (CHX), an inhibitor of translation, suggesting that it is partially caused by induced expression. Functional activation was reversed by modulators of the endothelin receptor (ETB)/nitric oxide synthase/protein kinase C signaling pathway. Transporter activating effects were reversed by Gö6976 and peptide C2-4, both being PKCα inhibitors. Cu(ATSM)-induced activation was further suppressed by phosphatidylinositol 3-kinase inhibitor LY-294002 and mTOR inhibitor rapamycin. Activation was also inhibited by GSK650394, an inhibitor of serum-and-glucocorticoid-inducible-kinase-1 being a subsequent target. Given the parallelism with other metals, this ABC transporter regulation appears to be a general defense mechanism of teleosts to react on metallic pollutants.